The Role of Green Human Resource Management on Employee Behavior and Corporate Environmental Performance in Indonesian Sharia Banks - Rosya Mawaddah Susanto; Siswanto Siswanto; Yayuk Sri Rahayu (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The growing number of companies focusing on environmental preservation and the limited literature on green human resource management in the Islamic banking industry make this an intriguing topic for deeper research. This study explored the impact of environmental green human resource management on environmental engagement and corporate environmental performance in the Sharia banking industry. This investigation also explores the mediating effect of Green Organizational Culture on the relationship between Green Human Resource Management and both environmental engagement and corporate environmental performance. Using quantitative methods, Smart-PLS analysis was used to perform structural equation modeling (SEM). A total of 116 data respondents were selected using random sampling from Sharia banking employees in East Java, Indonesia. The results showed that Green Organizational Culture has a positive impact on environmental engagement and corporate environmental performance. Green Organizational Culture fully mediates the impact of Green Human Resource Management on environmental engagement and corporate environmental performance. The implications of this study suggest that companies should embed environmentally friendly values into their vision and mission and cultivate an organizational culture that embodies these values.